Development of competencies at the university libraries: Human Resource of the library of the faculty of human sciences and Islamic sciences University of Oran 1 Ahmed Ben Bella, Algeria - Miloud, LARBI BENHADJAR; Kheira, MAMMAD; Ali, MOULAY (Journal of Humanities & Social Sciences, 2021)
This study aimed at cast the light on the strategy of human resources management and the development of competencies in university libraries, with particular emphasize on their importance and their general application, and to examine the steps undertaken by those libraries to achieve their objectives. The aim of this study is to focus on the importance of managing and developing competencies in university libraries, knowing the requirements that information specialists should have in the information age, and how they apply the competency management strategy, in order to have good results and recommendations for those involved in choosing the best management strategies. University libraries face challenges, the most important of which are the successive and rapid developments, the knowledge explosion, and the complexity of the work environment, that prompts us to ask the following key question: What is the effective strategy of human resources management in the development of competencies in university libraries? This study aims at examining an important human resource theme, which seeks to develop the competence of the human element and to provide it with a qualification to cope with modern day, and to provide it with scientific expertise and skills to gain the required qualification that enables it to move forward to the appropriate professional and social life. In order to reach satisfactory results, we have made four important hypotheses, since competency in university libraries is a strategy, the university library as a scientific research institution that can implement a competency management strategy, and the management of human resources can exploit its competencies by developing clear management plans and working to attract and maintain competencies by constantly monitoring and evaluating their performance. Human resources management at university libraries can develop staff competencies with ongoing training, guidance and motivation. In our study, we relied on the descriptive- analytical approach, which is based on the description and analysis of phenomena, to reach conclusions and to prove the validity of this investigation. Results of our study suggest, good social ties and human relations enhance understanding among staff within the library, which positively reflects the workflow in the first place, however the regular and periodic training programs help improve the services of the university library, and the management at three levels and the human resource as being the most important resources of the university library. Our findings suggest that competencies are important in human resources as well as polarization and evaluation performance, as well as to develop their competence through training and motivation. Moving from individual to a team competence, and to shift from specialization to multi- competency in all jobs, making the development of competencies a priority of management strategy.